PENGARUH KAPABILITAS KETUA KOMISARIS DAN DIREKTUR UTAMA TERHADAP PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DENGAN KONTROL KELUARGA SEBAGAI VARIABEL MODERASI - Khayla Diani Putri; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2026)
This research aims to examine the effect of Chairman and Chief Executive Officer (CEO) capability on ESG disclosure, with family control as a moderating variable in family firms listed on the Indonesia Stock Exchange during the period 2020-2023. Based on Agency Theory, this study employed purposive sampling and selected 20 family firms, resulting in 80 observations tested using Moderated Regression Analysis (MRA). Leadership capability was measured through a four-dimensional composite index, family control was measured through three dimensions, and ESG disclosure was measured using 85 GRI Standards indicators. The results indicate that Chairman capability has a significant positive effect on ESG disclosure, while CEO capability does not have a significant effect. Family control is proven to weaken the positive effect of Chairman capability on ESG disclosure, but does not significantly moderate the relationship between CEO capability and ESG disclosure.